The Effect of High-Intensity Interval Training on Pencak Silat Athletes - I Gede Berata; Kadek Yogi Parta Lesmana; I Ketut Semarayasa (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
High Intensity Interval Training (HIIT) is currently one of the training methods that are widely applied to improve athletic performance in various sports. This method emphasizes a combination of high-intensity physical activity performed in a short duration and interspersed with relatively short rest periods. In the context of traditional martial arts, especially pencak silat, athletes are required to have a high level of muscle strength, cardiovascular stamina, speed, and agility to support the effectiveness of attack and defense techniques during the match. Therefore, the application of the right training method is an important factor in supporting the achievements of pencak silat athletes. This research paper aims to examine the impact of the application of HIIT on improving the physical performance of pencak silat athletes. The research method used is a literature review by analyzing a number of relevant national and international journals published in the range of 2019–2025. Data were obtained from scientific articles that had been indexed by SINTA and Scopus, then analyzed qualitatively descriptively based on the research theme, findings, and theoretical implications reported. The results of the study show that HIIT has a significant influence on increasing cardiovascular endurance, muscle strength, and agility, which are the main components of physical condition in pencak silat. With its efficient characteristics in terms of time and intensity, HIIT has the potential to be an effective and applicable alternative training program for pencak silat athletes in an effort to improve overall physical performance.